Pengeringan Kopi Robusta (Coffea canephora) Menggunakan Rumah Pengering Hybrid Tipe Rak - Wicaksono, Yoga Arif; Warji, Warji; Tamrin, Tamrin; Kuncoro, Sapto (Jurnal Agricultural Biosystem Engineering, 2023)
Coffee is one of the mainstay plantation commodities in Indonesia. In 2015 Indonesia had a coffee plantation area of 1,254,382 hectares, with a production of 379,005 tons. Coffee is one of the mainstay commodities in Indonesia's plantation sector. The role of coffee commodities for the Indonesian economy is quite important, both as a source of income for coffee farmers, a source of foreign exchange, a producer of industrial raw materials, and a provider of employment through processing, marketing, and trade activities (exports and imports). The Robusta coffee drying process will result in the dried product experiencing changes in color, texture, and aroma. The purpose of this study was to analyze the characteristics and drying process of Robusta coffee using a rack-type hybrid drying house with three treatments, namely, drying with a drying house using solar energy, drying with a drying house using solar energy and gas energy (hybrid) and conventional drying. The length of time to dry 10 kg of Robusta coffee to approximately 11.5% moisture content is for drying with a drying house using solar energy takes 96 hours or 12 days, for drying with a drying house using solar energy and gas (hybrid) takes 80 hours (10 days) and for drying using tampah (conventional) takes 104 hours (13 days). Keywords: Dryer, Hybrid, Robusta Coffee.